Efficacy of Xylanase Supplementation Produced from Thermoascus aurantiacus SL16W in Diet on Thai Native Chicken Performance - Kongbuntad, Watee; Khanongnuch, Chartchai; Lumyong, Saisamorn (International Journal of Poultry Science, 2006)
The aim of this study was to determine the efficacy of xylanase supplementation in the diet on Thai native chicken performance. 36 birds (12 birds /group) were divided into three groups. The first group was administered a control diet and the second and third group were fed an experimental diet with two different levels, 10g/kg and 30g/kg, respectively. Live weight, feed intake, survivability the primary toxicity effect on organ weights and plasma biochemistries were recorded and evaluated. The results indicate that xylanase supplementation improves Thai native chicken performance by increasing live weight and decreasing feed conversion efficiency (FCE) and has no effect on survivability. Xylanase supplementation lead to a decreased blood urea nitrogen (BUN) level in 30g/kg diet, but was a slightly increased serum glutamic pyruvic transaminase (SGPT) levels. In addition xylanase supplementation had no effect on the internal organs. Therefore, it can be concluded that xylanase supplementation efficiently can improve Thai native chicken.